INCREASING THE QUALITY OF RURAL ENVIRONMENT WITH EMPHASIS ON GOOD GOVERNANCE FROM THE VIEWPOINT OF RESIDENTS OF VILLAGES OF THE CENTRAL PART IN ARDABIL, IRAN - Imani, Bahram; Rahmati, Mansour (Geosaberes; Vol 11 (2020): Vol 11 (2020)DO - 10.26895/geosaberes.v11i0.929, 2020)
Good governance is an adaptive approach in territorial planning and resource management for achieving sustainable development that can be reached through the regular behavior and institutionalization of accountability, public participation, transparency, accountability, consensus and etc. Rural governance is the process of influencing all the rural involved organizations on rural management with all mechanisms with which we can move towards the excellence and progress of the village and the rural residents. In Iran, the rural governance structure was formed on the basis of two principles of the Rural Islamic Council as a decision-making body and village management as an executive body. It enjoys legal and financial independence and in addition to using national tolls, has the ability to set up and collect local tolls for providing public services. The present study has been conducted in 2016 aimed to investigate the enhancement of rural environmental quality with an emphasis on good governance from the viewpoint of rural residents. This study is applied in terms of purpose and descriptive-analytic based on nature. The study population composed of 41 villages in the central part of Ardabil which were divided into 8 classes based on the number of households. From each class, one high populated and one low populated village was selected and finally 21 villages were selected. The sample size was estimated n = 370 according to Cochran formula. The library and field methods (questionnaire) were used to collect the required information. The data were analyzed using Kolmogorov-Smirnov, sample t and Friedman tests. The results indicate that good governance in the field of environment is not in a desired situation. Also, a significant difference was found in the effect of good governance dimensions on the environment, with the highest effect related to the participation index and the least effect related to equity and justice.